Donald Trump in historical perspective dead precedents - Harvey, Michael 1960- (Routledge, 2022)
"Donald Trump in Historical Perspective: Dead Precedents is a collection of essays that utilizes the thinking of historians, philosophers, and political scientists to explore historical parallels to the presidency of Donald J. Trump, the 45th President of the United States of America"--
Keywords: Trump, Donald -- 1946-; Geschichte; Vergleich; Politische Führung; Politischer Stil; Autoritarismus; Trump, Donald / 1946-; Trump, Donald / 1946- / Influence; Political leadership / United States; United States / Politics and government / 2017-2021; États-Unis / Politique et gouvernement / 2017-2021; Influence (Literary, artistic, etc.); Political leadership; Politics and government; United States; 2017-2021; Aufsatzsammlung